2023
DOI: 10.2147/idr.s425728
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Antibiotic Resistance Patterns and Burden of Escherichia Coli Infections in Young Children: A Retrospective Cross-Sectional Study in Shenzhen, China from 2014–2018

Sandip Patil,
Hongyu Chen,
Yunsheng Chen
et al.

Abstract: Purpose The emergence of multi-drug resistant ESBL-producing E. coli poses a global health problem. In this study, we aimed to investigate the prevalence of E. coli infections and their antibiotic susceptibility profiles in paediatric clinical cases in Shenzhen, China from Jan 1, 2014, to Jan 30, 2019, while also determining temporal trends, identifying ESBL-producing strains, and recommending potential empirical antibiotic therapy options. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our results correspond to the literature data on increasing levels of Gram-negative bacteria isolation (E. coli, Klebsiella spp.) in European countries, including bacteria presenting resistance mechanisms [44,45]. Also, Lagacé-Wiens et al reported significantly higher ESBL production in K. pneumoniae, E. coli, and moderately, in E. cloacae [46].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results correspond to the literature data on increasing levels of Gram-negative bacteria isolation (E. coli, Klebsiella spp.) in European countries, including bacteria presenting resistance mechanisms [44,45]. Also, Lagacé-Wiens et al reported significantly higher ESBL production in K. pneumoniae, E. coli, and moderately, in E. cloacae [46].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, under the Antimicrobial Testing Leadership and Surveillance (ATLAS) programme, the global prevalence of ESBL(+) E. coli was found to be 23.7% and K. pneumoniae 35.1% in 2017-2019 [50]. In retrospective studies conducted on children in Shenzhen, China (2014-2018), as much as 49.54% of E. coli strains synthesised ESBLs; however, a downward trend was observed over time [45]. In the present study, 82 of 905 E. coli isolates (9.06%) were ESBL(+), but this resistance phenotype was more commonly observed in K. pneumoniae (113 of 252 isolates; 46.03%).…”
Section: Discussionmentioning
confidence: 99%
“… 1 The emergence of MDR- E. coli has garnered significant attention in several countries, necessitating alternative therapies to address this issue. 2 , 3 One such approach is the utilization of phage therapy. However, as highlighted by the authors in their article, the emergence of phage-resistant variants presents a new challenge, thus underscoring the perceived necessity of employing phage cocktails as a therapy strategy.…”
Section: Dear Editormentioning
confidence: 99%